Relationship between Third Trimester Vaginal Bleeding Medical Causes and pregnancy Outcomes of Pregnant Women Attending Bint Al-Huda Hospital in Al-Nasiriya City - Kadhim, sarah; khairi, suhad (Iraqi National Journal of Nursing Specialties, 2016)
Objective: To find out the relationship between vaginal bleeding during third trimester and pregnancy outcomes. Methodology: A purposive sample is "Non-probability" of (100) women who had diagnostic vaginal bleeding during third trimester (27-40wk) of pregnancy, and who visited the Bint Al-Huda Hospital for the period from 15th Feb. to 17th May 2015.Validity and reliability of questionnaire are determined through pilot study. Descriptive and inferential statistical procedures were used to analyze the data, and the data were collected by using interview technique, constructed questionnaire has been designed in three parts: socio demographic, reproductive data and questions related to current vaginal bleeding and medical Causes, and pregnancy Outcomes. Results: Results of the study showed that the highest percentage of the study sample were within the age group (20-24 years). And women with high educational and economic level and more than half of the study sample were housewives, and residents in urban areas. With regard to the information reproductive the highest percentage of the study sample had been pregnant for five times and had given birth five times and more and have at least four living children were pregnancy in weeks period (28-29) a week and (30-31) a week, respectively, and the interval between the last pregnancy and current one year to two years. And that the cause of bleeding from a medical point is the rupture of the uterus and attributed the causes of bleeding from their medical point of view were accidents. The study shows that the impact on the newborn was premature birth of a child and that there is a significance relationship between the medical causes of 3rd trimester vaginal bleeding and pregnancy outcomes. Recommendations: Increases pregnant women awareness about pregnancy complications especially bleeding during pregnancy through mass media, pay more maternal attention and Emphasize the importance of attending the primary health care center for antenatal care to early diagnosis and treatment of some possible complications during pregnancy, reduce the number of pregnancy especially for those with high risk through family planning and Reduce the perinatal morbidity and mortality through good neonatal intensive care facilities.